Living in the Extreme: Fatty Acid Profiles and Their Specificity in Certain Tissues of Dominant Antarctic Silverfish, Pleuragramma antarcticum, from the Antarctic Sound (Southern Ocean) Collected during the Austral Summer - Svetlana N. Pekkoeva; Viktor P. Voronin; Aleksej V. Mishin; Alexei M. Orlov; Svetlana A. Murzina (Diversity, 2022)
The fatty acid profile of seven different organs (brain, gills, heart, muscles, gonads, liver, and gall bladder) of the lipid-rich Antarctic silverfish, Pleuragramma antarcticum, from the Antarctic Sound was studied. Qualitative and quantitative analyses of fatty acids were performed using gas chromatography with mass-selective and flame ionization detectors. It was seen that the muscles and gills differed from the other organs with the prevalence of saturated fatty acids, mainly due to 16:0 and 14:0 that may reveal their additional metabolic role in these organs for adaptation of the fish to the cold Antarctic waters. Monounsaturated fatty acids 18:1(n − 9) and 16:1(n − 7) were prevalent in the other organs of silverfish, especially their high content in the liver, reflecting the carnivorous feeding type (mainly adult ice krill) of the species and their dietary preferences in the austral summer. The high content of essential fatty acids, 22:6(n − 3) (14% of total fatty acids) found in the brain and 20:5(n − 3) (12% of total fatty acids) found in the muscles, highlights the functional significance of these lipid components in the studied tissues of fish. The results will improve the understanding of the functional value of individual fatty acids in terms of their organ specificity and the adaptation of the Antarctic silverfish to life in the frigid ice waters of the Antarctic pelagic ecosystem.